Olfactory responses of the leafhopper vector Mgenia fuscovaria (Stål) (Hemiptera : Cicadellidae) to volatiles from aster yellows phytoplasma-infected and uninfected grapevine (Vitis vinifera L.) - Kruger, Kerstin (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.